3 Statutes at Large of Pennsylvania from 1682 to 1801 255-256 (1896) - (:unkn) unknown (My University, 1721)
"if any person or persons shall presume . . . to carry any gun or hunt on the improved or inclosed lands of any plantation other than his own, unless he have license or permission from the owner of such lands or plantation . . . he shall for every such offense forfeit the sum of ten shillings."
Keywords: PRIVATE PROPERTY POSSESSION BAN